Dissolved and Suspended Forms of Metals and Metalloids in Snow Cover of Megacity: Partitioning and Deposition Rates in Western Moscow - Dmitry Vlasov; Jessica Vasil’chuk; Natalia Kosheleva; Nikolay Kasimov (Atmosphere, 2020)
Concentrations and ratio of dissolved and suspended forms of metals and metalloids (MMs) in snow cover and their deposition rates from the atmosphere in the western part of Moscow were studied. Forms of MMs were separated using a filter with pore diameter of 0.45 μm; their concentrations were measured by ICP-MS and ICP-AES methods. Anthropogenic impact in Moscow caused a significant increase in dust load (2–7 times), concentration of solid particles in snow cover (2–5 times), and mineralization of snow meltwater (5–18 times) compared to the background level. Urban snow contains Sn, Ti, Bi, Al, W, Fe, Pb, V, Cr, Rb, Mo, Mn, As, Co, Cu, Ba, Sb, Mg mainly in suspended form, and Ca and Na in dissolved form. The role of suspended MMs in the city significantly increases compared to the background region due to high dust load, usage of de-icing salts, and the change of acidic background conditions to alkaline ones. Anthropogenic emissions are the main sources of suspended Ca, W, Co, V, Sr, Ti, Mg, Na, Mo, Zn, Fe, Sb, and Cu in the snow cover of traffic zone. These elements’ concentrations in roadside snow cover exceed the background values more than 25 times. The highest concentrations and deposition rates of MMs in the snow of Moscow are localized near the large and medium roads.